Comparison of Felodipine and Propranolol in the Treatment of Hypertension (Medical Forum Monthly, 2024)
Objective: To compare the efficacy of felodipine and propranolol in the treatment of essential hypertension.Study Design: Randomized controlled studyPlace and Duration of Study: This study was conducted at Accident and Emergency Department, Bahawal Victoria Hospital Bahawalpur and Ansari Private Clinic Model Town B, Bahawalpur from March 2013 to May 2013.Materials and Methods: Total 90 patients of mild to moderate essential hypertension both male and female between the ages of 30 to 55 years were enrolled to this study, for 90 days patients were randomly divided into three groups Group I, II and III. Efficiency of felodipine, propranolol and placebo tablets in the treatment essential hypertension was compared.Results: Felodipine and propranolol both reduces the systolic blood pressure was highly significant (P<0.001) between day 0-15, day 0-30, day 0-45, day 0-60, day 0-75 and day 0-90. The placebo exhibited a non-significant effect on systolic blood pressure.In case of diastolic blood pressure patients treated with felodipine and propranolol the decrease of blood pressure was also significantly (P<0.001) for all time intervals. In placebo administered group the effect of diastolic blood pressure was non-significant at all-time intervalsConclusion: Result of this study showing that both felodipine and propranolol significantly reduces blood pressure at all time of intervals. In addition felodipine has got an edge on propranolol that it is administered once daily.